2022
DOI: 10.3390/healthcare10030560
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Aquatic Exercises for Patients with Osteoarthritis: Systematic Review with Meta-Analysis

Abstract: This systematic review examined papers published in Korean, English and newer publications that were not included in previous studies to assess the effect size of aquatic exercise-based interventions on pain, quality of life and joint dysfunction among patients with osteoarthritis. Six national and international databases were used to review literature (published up to 7 March 2019) on randomized controlled trials of aquatic exercise-based interventions in patients with osteoarthritis. For the 20 studies inclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 41 publications
(100 reference statements)
1
7
0
Order By: Relevance
“…Exercise, regardless of setting, can increase joint strength and range of motion leading to improved joint function. However, the incidence of osteoarthritis is high in overweight patients, and the buoyancy of water supports body weight, thereby reducing the impact on joints, this helps reduce pain and facilitates movement (Song and Oh, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Exercise, regardless of setting, can increase joint strength and range of motion leading to improved joint function. However, the incidence of osteoarthritis is high in overweight patients, and the buoyancy of water supports body weight, thereby reducing the impact on joints, this helps reduce pain and facilitates movement (Song and Oh, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…However, some popular forms of exercise, such as walking, using treadmills, or cycling, are noteworthy for their popular adoption and their positive reception by patients. Additionally, aquatic exercises serve as a valuable tool in OA management, strengthening the benefits of aerobic activity while significantly reducing the strain on the joints in a water-based environment [143]. Tai chi is highly recommended in individuals with knee or hip OA, as it has demonstrated effects on both physical and mental well-being [142].…”
Section: Physical Treatments In Oamentioning
confidence: 99%
“…An earlier systematic review of RCTs assessing the effectiveness of water-based exercise on KOA found that this approach results in improvements in self-reported pain and disability, but that the effect seems to be of a small magnitude and short duration [53]. Recently, another systematic review and meta-analysis with more specific recommendations was conducted [54] based on RCTs involving administered water-based exercise programs in pools in which the water was between waist and chest height and at a temperature of 28-34…”
Section: • Formal Exercisementioning
confidence: 99%
“…• C, with a duration/session of 50 to 60 min for two to five sessions/week, and over an intervention program period of 12 weeks. These interventions were found to alleviate pain, improve the quality of life and reduce dysfunction [54] (Table 3). However, more research is still needed to clarify the exact type of such water-based exercise.…”
Section: • Formal Exercisementioning
confidence: 99%